Study guides

☆☆

Q: 6x - 8 plus 2x - 5 equals 7 - 2x?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

6x-8+2x-5 = 7-2x 6x+2x+2x = 7+8+5 10x = 20 x = 20/10 x = 2

4x - 5 + 2x = 376x - 5 = 376x = 37 + 56x = 42x = 42 / 6x = 7

6x + 5

24x^3 + 72x2 + 30x = 6x*(4x^2 + 12x + 5)=6x*(2x + 1)*(2x + 5)

6x2 + 10x = 2x*(3x + 5)

Related questions

6x + 3 = 2x + 5 4x = 2 x=1/2

6x-8+2x-5 = 7-2x 6x+2x+2x = 7+8+5 10x = 20 x = 20/10 x = 2

6x - 3y = 6 y= 2x + 5 replace 2x + 5 for y into the first equation 6x - 3y = 6 6x - 3(2x + 5) = 6 6x - 6x - 15 = 6 0 - 15 = 6 -15 = 6 False So the system has no solution.

6x - 5 + 2x = 116x + 2x - 5 = 118x - 5 = 11Add 5 to each side:8x = 16Divide each side by 8:x = 2

x=5. 10x-4x (6x) +10-6x (=10) If 10 is 2x, x=5.

4x-15=6x-4x 4x-22.4=2x 2x=22.4 x=11.2

6x - 5 = 19 + 2xAdd 5 to each side:6x = 24 + 2xSubtract 2x from each side:4x = 24Divide each side by 4:x = 6

4x - 5 + 2x = 376x - 5 = 376x = 37 + 56x = 42x = 42 / 6x = 7

The value of X in the equation 2x-1-6 5 plus 6x is -3.

6x + 8 = 6 6x = -2 x = -2/6 x = -1/3

6x + 5

2x + 5 = 7 - 4x ie 2x + 4x = 7 - 5 ie 6x = 2 x = one third.

People also asked